An experimental study exploring the impact of vignette gender on the quality of university students’ mental health first aid for peers with symptoms of depression - Davies, E. Bethan; Wardlaw, John; Morriss, Richard K.; Glazebrook, Cris (BioMed Central, 2016)
Background